Progress in acetylcholinesterase reactivators and in the treatment of organophosphorus intoxication: a patent review (2006-2016) - Gorecki, Lukas; Korabecny, Jan; Musilek, Kamil; Nepovimova, Eugenie; Malinak, David; Kucera, Tomas; Dolezal, Rafael; Jun, Daniel; Soukup, Ondrej; Kuca, Kamil (Expert opinion on therapeutic patents, 2017)
organophosphorus compounds act as irreversible inhibitors of the vital enzyme acetylcholinesterase (AChE). this leads in the accumulation of acetylcholine (ACh) leading to cholinergic crisis and death. The main therapeutic approach is based on immediate administration of an ache reactivator as an antidote enabling recovery of the ache function. Areas covered: This review covers the development of AChE reactivators in order to introduce a new efficient drug that will overcome significant failures of common antidotes. Further options together with methods of detection are also discussed in order to assure a complete insight into the treatment of intoxication. Expert opinion: Since organophosphates belong to the most toxic chemical warfare agents, efficient antidotes are a matter of importance. The solution of how to limit the basic drawbacks of clinically used reactivators remained a spotlight for many researches worldwide. Recent strategies of the treatment of OP exposure bring us new possibilities which may overcome classic antidotes. The importance of detection of OP also has to be taken into consideration. Especially, with the fast spreading toxic effect when death can occur within minutes.
Keywords: patenty jako téma; Animals; identification; Acetylcholinesterase; Chemical Warfare Agents; antidota; nerve agents; Organophosphorus Compounds; otrava organofosfáty; lidé; chemické bojové látky; Antidotes; organofosforové sloučeniny; reactivators; organophosphate; catalytic bioscavengers; acetylcholinesterasa; racionální návrh léčiv; reaktivátory cholinesterasy; Drug Design; Patents as Topic; zvířata; methods of detection; cholinesterasové inhibitory; Cholinesterase Inhibitors; Organophosphate Poisoning; Cholinesterase Reactivators; Humans